Perspective of Islamic Economics: Consumptive Behavior of Online Shopping and The Paylater System - Hasanuddin, Hasanuddin; Alrasyid, Harun; Malik, Abdul (Perbanas Journal of Islamic Economics and Business, 2024)
Advancements in technology and the internet have influenced the consumer behavior of society, including students. This phenomenon has become more evident with the ease of online shopping and the use of the Paylaterpayment system. From the perspective of Islamic economics, this consumptive behavior raises questions about its alignment with recommended principles. This research aims to analyze the consumptive behavior of students in online shopping using the Paylater system from an Islamic economic perspective. The study also seeks to understand the impact of the ease of online shopping on consumptive behavior and how it aligns with Islamic economic principles.Most previous research has focused more on consumer behavior in general or within the context of conventional economics. There is still little research that specifically examines consumptive behavior in online shopping using the paylater system from an Islamic economic perspective, especially involving students as research subjects. The research method used is qualitative with a phenomenological approach. The research results indicate that the consumptive behavior of students in online shopping is influenced by the convenience and ease offered by the paylater system. From the perspective of Islamic economics, this behavior can be considered inappropriate as it encourages purchases not based on actual needs but rather on desires or prestige. Islam emphasizes meeting needs in a simple way and avoiding wasteful or extravagant behavior.This research has important implications for educational policies and the regulation of financial technology usage among students. There is a need for education on the importance of prudent financial management in accordance with Islamic economic principles. Additionally, the results of this study can serve as a basis for developing stricter policies related to the use of the paylater system to reduce excessive consumptive behavior.